MANAJEMEN KOLABORASI SEKOLAH DENGAN ORANG TUA TERHADAP PERKEMBANGAN ANAK USIA DINI - Eliyana Eliyana; Muhajirin Ramzi (STKIP Pesisir Selatan, 2026)
This study aims to analyze the management of school-parent collaboration on early childhood development, describe the forms of collaboration implemented, and identify supporting and inhibiting factors. A synergistic partnership between the child's two primary environments is crucial to ensuring the continuity of educational stimulation. This study used a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with school principals, teachers, and parents, as well as through participant observation and program documentation. The results indicate that the implemented collaborative management includes planning a partnership program (parenting), organizing equal roles, implementing it through two-way communication channels (connection books, digital media, and parenting classes), and regular evaluation of children's developmental achievements. Well-managed collaboration has been shown to have a significant impact on children's holistic development, encompassing moral and religious values, physical-motor skills, cognitive skills, language skills, and socio-emotional skills. The main supporting factors are the school's openness and the parents' proactive attitude, while the biggest obstacles lie in the limited time of working parents and differing perceptions of parenting styles. This study recommends the need for innovative, more flexible partnership programs to bridge the gap between parents' time constraints.